The menstrual phase does not impact chemosensitivity during exercise - Leah M. Mann; Madeline D. Wright; Benjamin P. Thompson; Jou‐Chung Chang; Jason S. Chan; Glen E. Foster; Paolo B. Dominelli (Physiological Reports)
Abstract At rest, the menstrual cycle phase impacts ventilation and chemosensitivity. However, during exercise there is inconclusive evidence that the menstrual cycle phase affects ventilation or chemosensitivity. We sought to examine the influence of menstrual phase and hormonal birth control (BC) on chemosensitivity. We tested 12 males and 20 females (10 BC; 10 normally menstruating, NBC) on three occasions. Day 1 was a maximal exercise test and days 2 (follicular phase) and 3 (luteal phase) consisted of three bouts of chemosensitivity testing during cycle exercise at 30% of peak work rate. Females‐BC and males completed day 3 approximately 2 weeks after day 2, with females‐BC tested during the active phase of their birth control. There were no differences between the two experimental days for any groups for any (hypercapnia, hypoxia, and hyperoxia) chemosensitivity tests, p > 0.05. Females‐BC had a significantly lower average response to transient hypercapnia than both females‐NBC and males (38% and 42% lower, respectively, p < 0.05). Females‐NBC had a significantly smaller change in ventilation to hyperoxia compared to males, −11.7 ± 5.9 versus −17.9 ± 5.4%, respectively (p < 0.05). We conclude that the day‐to‐day variability in chemosensitivity is not different between males, females‐BC and NBC.